PRÁTICAS E NORMAS CULTURAIS NO ENSINO DE CIÊNCIAS: UMA EXPERIÊNCIA DOCENTE NA ESCOLA PÚBLICA - Reis, Anazia Aparecida (2021)
The transposition of the National Common Curriculum Base into the classroom brought insecurity to science teaching professionals because they base their teaching practice on experiential experiences. Based on the premise that teaching professionals build knowledge in their professional practice, this dissertation investigates the conditions that bring a science teaching plan from the final years of elementary school to cultural practices and norms in science teaching. Through a teaching narrative, almost four school years (2017-2020) of teaching are described in a public school on the outskirts of Greater Vitória, in Espírito Santo. Four activities in this teaching plan are identified: diagnosis, classes, written work and science fair. It also identifies the complete set of cultural practices and norms in science teaching at the Science Fair 2017, 2018 and 2019, in the Classes of 2018, 2019 and 2020 and, in the Written Work of 2018 with the 6th year and 8th year. The search for the conditions that brought these activities closer to cultural practices and norms in science teaching revealed two premises of the teaching practice investigated: problematization and the protagonism of students. Another discovery of this search was the articulation between the activities of the teaching plan. The Diagnosis was an activity responsible for investigating the role of students in the production of knowledge in the specific context of that school. This research rebuilt the Classes and thus made them achieve the complete set of cultural practices and norms in science teaching. The Classes articulated the proposal of teaching the network to problematization and the protagonism of students. The written Work reached all cultural practices and norms in the teaching of sciences when the theme and content came from the Classes and the problem investigated, derived from the reality of students. The Science Fair was the activity with the greatest role of students in the construction of knowledge because they allowed them to choose the theme and the problem to be investigated. Thus, it is concluded that the conditions that bring this teaching plan closer to the practice and norms of science teaching are articulation between activities with the premise of developing the protagonism of students in the construction of knowledge in science classes.